How citizen science boosted primary knowledge on fungal biodiversity in Denmark. (September 2019) - Heilmann-Clausen, Jacob; Bruun, Hans Henrik; Ejrnæs, Rasmus; Frøslev, Tobias Guldberg; Læssøe, Thomas; Petersen, Jens H.
Abstract: The Danish Fungal Atlas was a citizen science project aiming to map Danish macrofungi over five years (2009–13). The atlas contributed >235, 000 records of fruit-body forming Basidiomycota, adding to about 195, 000 fungal records from earlier periods. The new records increased the average number of species known per 10 km × 10 km grid cell by 75% from 125 to 218 species. We recorded 197 species as new to Denmark, extending the number of known basidiomycote species by 7%. At least 15 species appeared to be new to science. Among the new Danish records, species with northern distribution ranges were significantly overrepresented, in marked contrast to climate change predictions. Species with inconspicuous or subterranean fruit bodies were overrepresented among both the new Danish species and those only recorded before the project period, indicating low recording probability to be an important driver for the turnover in species recorded. Hence, the main drivers of novel fungal discoveries were 1) intensive sampling effort by citizen scientists guided by professional mycologists and 2) improved taxonomic knowledge. Summarizing over the last 100 years, an exponential increase in known macrofungal diversity in Denmark is evident, suggesting that we are still far from having a complete overview. This is striking, considering that Denmark is among the best-studied land areas on the globe. We conclude that citizen science projects, if appropriately designed, have a huge potential to boost primary knowledge on fungal biodiversity. Highlights: Citizen science is in its infancy as a tool to explore fungal diversity. A five year citizen science project on macrofungal diversity in Denmark Increased knowledge, effort and improved tools drove new species discovery. No evidence of changes in the Danish species pool due to climate change Species sensitive to soil acidification and nitrogen deposition were lost.